2014
DOI: 10.1080/21622965.2013.874951
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes: Long-Term Central Nervous System Developmental and Cognitive Sequelae

Abstract: Gestational diabetes is a common complication of pregnancy and occurs in approximately 7% of all pregnancies. It has been associated with an increased rate of congenital anomalies including disturbances of intrauterine growth, delayed brain maturity, and neurobehavioral abnormalities in the offspring. The resulting maternal and fetal metabolic dysfunction leads to diminished iron stores (which can affect red blood cell [RBC] production and subsequent organogenesis), a metabolism-placental perfusion mismatch, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…28 In our study, the offspring of diabetic dams presented neurodevelopmental delay in the negative geotaxis test according to and complementing the cognitive impairments reported by the clinic. 29,24 Furthermore, a decrease in the object recognition index this is in agreement with the results of Kim et al 30 who have demonstrated, with the same experimental model, impaired memory in stepdown avoidance task on PND42.…”
Section: Recognition Index (%)supporting
confidence: 90%
See 1 more Smart Citation
“…28 In our study, the offspring of diabetic dams presented neurodevelopmental delay in the negative geotaxis test according to and complementing the cognitive impairments reported by the clinic. 29,24 Furthermore, a decrease in the object recognition index this is in agreement with the results of Kim et al 30 who have demonstrated, with the same experimental model, impaired memory in stepdown avoidance task on PND42.…”
Section: Recognition Index (%)supporting
confidence: 90%
“…Compelling evidence have shown that this maternal type 1 diabetes model can induce microsomia in the offspring, possibly as a result of intrauterine growth restriction with placental commitment, 20,22,23 leading to long-term effects, especially in metabolic and neurologic parameters in the infants. 24,25 The continuation of the hyperglycemic status in diabetic dams (D) after parturition seemed to contribute to the reduced growth during suckle, and pups remained small until weaning age (PND 21) as previously described by Chandna et al 26 The observed effects in offspring may not be only due to the gestational diabetes, but also to the malnutrition at early stages of offspring development, since that maternal type 1 diabetes can delay lactogenesis onset by affecting prolactin secretion and lactose, citrate, and total nitrogen concentrations in the milk. 27 On the other hand, in the offspring of diabetic dams treated with ginger (D + G), our results showed an increase in body weight, which may be due to the decrease in maternal blood glucose after treatment with ginger extract and stimulation of lactation in these dams.…”
Section: Recognition Index (%)mentioning
confidence: 99%
“…Moreover, these children were characterized by a higher rate of inattention and/or hyperactivity. Though most newborns are not significantly affected by gestational diabetes, in clinical practice this condition has been often associated with lower general intelligence, language impairments, attention weaknesses, and behavioral problems (Perna et al, ). Infants born to diabetic mothers show a higher frequency of impaired neurodevelopment, confirming the hypothesis that maternal diabetes may result, at least in some cases, in an insult for the developing fetal brain (Aguilar Cordero et al, ).…”
Section: Maternal Factorsmentioning
confidence: 99%
“…However, with the limitation of the small number of patients in our study, there was no statistical difference between the two groups. In addition to increased risks for birth complications recent data also have demonstrated increased risks for children born by mothers with gestational diabetes to develop obesity/diabetes and also neurodevelopmental disorders (ADHD) [25].…”
Section: Discussionmentioning
confidence: 99%
“…From June 2015 to March 2016, 40 patients (24-28 gestational weeks, singletons) with gestational diabetes mellitus and average age of 32±3.3 years (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) were enrolled from the pregnancy nutrition outpatient department of Peking University People's Hospital. The diagnostic criteria for gestational diabetes were according to the IADPPSG standard [6] as accepted by ADA.…”
Section: Subjectsmentioning
confidence: 99%